Relationship between depression and physical disability by gender among elderly in Indonesia - Ana Satria; Yeni Yeni; Hairil Akbar; Henny Kaseger; Linda Suwarni; Abubakar Yakubu Abbani; Maretalinia Maretalinia (Universa Medicina, 2022)
BackgroundThe increasing population of older people can be a positive impact if they could be productive, or it could be negative as a burden if they depend on others. Elderly with physical disabilities can be influenced by various factors, including depression, which can be caused by functional changes in the body due to aging, loss of work, or even the loss of a loved one. This study aimed to determine the relationship between depression and physical disabilities among the elderly in Indonesia who were stratified by gender. MethodsA cross-sectional study using a national survey dataset namely Basic Health Survey and Socio-Economic Survey for 2018 involving 85,427 elderly. Depression and disability were assessed using Mini International Neuropsychiatric Interview and Barthel Index. Chi-Square test and multiple binary logistic regression were used to analyze the data. ResultsThe results revealed that 24.75% of elderly people experienced physical disabilities. The probability of males and females with depression having physical disabilities was respectively 2.95 (95% CI = 2.74-3.17) and 2.49 (95% CI = 2.36-2.64) times higher compared to those without depression. The interaction between depression and gender was statistically significant, in that females with depression had an 11% probability of having physical disability. ConclusionThis study reaffirmed that disability is a risk factor for depression in the elderly and female gender is the effect modifier rather than the risk factor. The male depression group showed more physical disability symptoms than the female depression group. There is collaboration from various sectors to prevent depression and physical disabilities.